Dislodgement of hip arthroplasty into the psoas muscle: Case report of a rare complication and its management - Nidhi Chawla; Aliyah Stephens; Sanjay Thomas (Journal of Orthopaedic Reports)
Background: Posterior dislocations are the most prevalent, with an occurrence of about 90 % of all THA dislocation complications.1,2,6 The risk of dislocation after primary THA is about 2 %,1,3 while dislocation rates after revision surgery can increase up to 28 %.1-3,7 The increased sliding distance associated with larger heads may contribute to greater polyethylene wear.11-13 Despite advances, dislocations remain a persistent issue, especially in revision cases, highlighting the need for a comprehensive understanding of the risk factors and mechanisms that contribute to these complications. Case report: We present a case of a 73-year-old female who presented with anterosuperior prosthetic hip dislocation into the pelvis after a 10-year hip arthroplasty revision. The patient presented after a fall with anterosuperior dislocation of the left total hip prosthesis and a nondisplaced spiral fracture of the left hand. The patient underwent total hip arthroplasty revision with a Stryker +8 28 mm metal head. Written consent for the case report and the inclusion of diagnostic images was obtained from the patient's health care proxy. Conclusion: The presented case represents a rare instance of an anterosuperior hip dislocation into the psoas muscle following revision THA. These rather uncommon presentations necessitate the importance of personalized treatment approaches and a deeper understanding of the biomechanical factors unique to revision cases. Consequently, dislocation prevention is critical and an area that should be further investigated. This requires not only thorough preoperative risk assessment but also the use of precise surgical techniques, including optimal component alignment, soft tissue balancing, an appropriate head-neck ratio, and sufficient surgical expertise.